The AI Revolution in Patient Care: Can Artificial Intelligence Track Medication Adherence? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The AI Revolution in Patient Care: Can Artificial Intelligence Track Medication Adherence? Medication non-adherence—the failure to take medications as p...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning